Proposals For Solving Transport Problems In Large Cities - Khaydarov Shokhbozjon (Journal of Geography, Regional Planning and Development, 2024)
Transport system - an integral part of the modern world mobility system. The most basic element of this system is humans. It is also impossible to plan a transport system without taking into account passengers, as it is impossible to imagine unmanned transport in existing conditions.